Analisis Yuridis Penyelesaian Kredit Macet dengan Jaminan Hak Tanggungan di Bank PT. BPR Serang Cabang Pontang - DIAH PURNAMASARI (CV Rewang Rencang, 2025)
Business activities are always closely related to contracts or agreements. Agreements are made to bind the parties who make them and to determine the responsibilities and rights of each party. The submission of collateral in an agreement can be done to avoid default by one of the parties in the future. For example, in banking business activities provide credit facilities. Before the credit facility is granted, the creditor and debtor enter into a credit agreement and the contents of the agreement include the submission of collateral. One form of collateral that is widely used in the banking world is the Mortgage Right guarantee. The purpose of this study is to determine the form of legal responsibility of debtors due to default in credit agreements and to determine the mechanism for resolving bad debts with collateral. The method used in this research is normative legal research with a normative juridical approach using a statute approach and a conceptual approach. In this study, the researcher used primary legal materials, secondary legal materials, and non-legal materials. The data collection technique used was literature study and descriptive qualitative data analysis procedures. The results of the study indicate that in the provision of credit facilities, the creditor (BPR Serang) and the debtor entered into a credit agreement using a Mortgage Right as collateral. Then a problem arose where the debtor defaulted or neglected to pay the credit installments according to the specified time, resulting in bad debt. Efforts to resolve bad debts were made by BPR Serang Pontang Branch through rescheduling and restructuring, but the debtor still committed a default, so this requires new regulations to minimize the impact of losses. In conclusion, the party who defaults on the agreement must pay compensation, interest and fines, and if a default occurs, the agreement with a mortgage guarantee can be resolved by rescheduling, restructuring, and execution based on the Mortgage Law.